KARAKTERISTIK PERUSAHAAN DAN STRUKTUR MODAL USAHA KECIL DAN MENENGAH DI INDONESIA: ANALISIS DATA PANEL - Rachmaniar Myrianda Dwiputri; Najmudin Najmudin (Jurnal Fokus Manajemen Bisnis, 2021)
The purpose of this paper is to determine the firm’s characteristics and capital structure of SMEs registered in Indonesia. This study use panel data analysis for twenty-five firms over three years (2016-2018). The samples of this study were 25 Indonesian SMEs registered in the Pefindo25 index. The capital structure determinants are expressed as a function of size, tangible assets, current ratio, return on asset, and growth. This study used a pooled fixed effect to estimate the relationship between the variables. The result shows that the capital structure of registered SMEs in Indonesia is negatively affected by size, current ratio, return on asset, and growth. Registered SMEs in Indonesia have a capital structure that is in line with POT predictions.